Implementasi Akuntansi Lingkungan Terhadap Kinerja Perusahaan - Sintya Kirana; Nafisah Nuqma Nasyiwa (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the implementation of accounting on company performance. The method used in this research is literature study. The type of data used in this research is secondary data, which comes from research journals that have been reprocessed. This research instrument is data on accounting implementation on company performance. Where the journal is used as a reference, the determination of reference data comes from the internet and accredited journal website sources. Then the data obtained is analyzed, concluded and reviewed to obtain conclusions from the literature study. The results of the research show that benchmarks can be found regarding the implementation of accounting on company performance so that it can be concluded that there is an increased focus on environmental problems which is in line with increasing environmental damage. Despite repeated emphasis on the importance of environmental protection, environmental damage continues to occur, especially in relation to business operations. To overcome this problem, environmental accounting is considered the best solution for companies to be responsible for managing the impact of environmental damage related to their business activities. However, there are still challenges in implementing environmental accounting, mainly due to a lack of awareness among individuals and society. Several case studies in Indonesia, such as industrial waste dumping and uncontrolled deforestation, show that environmental violations can result in companies being closed down by the government.